2015
DOI: 10.1021/jp511548a
|View full text |Cite|
|
Sign up to set email alerts
|

Surface Enhanced Raman Scattering of Amino Acids Assisted by Gold Nanoparticles and Gd3+ Ions

Abstract: The surface enhanced raman scattering (SERS) signal from the l-tyrosine (tyr) molecule adsorbed on gold nanoparticles (Au-tyr) is compared with the SERS signal assisted by the presence of gadolinium ions (Gd(3+)) coordinated with the Au-tyr system. An enhancement factor of the SERS signal in the presence of Gd(3+) ions was ∼5 times higher than that produced by l-tyrosine adsorbed on gold nanoparticles. The enhancement of the SERS signal can be attributed to a corresponding increase in the local electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Raman spectroscopy and surface-enhanced Raman scattering were used to confirm the influence of Gd ions in Au–polymer nanoparticles. As described previously,23 the presence of Gd ions enhances the Raman signal of biomolecules (protein, natural polymer) capped onto gold nanoparticles (AuNPs).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Raman spectroscopy and surface-enhanced Raman scattering were used to confirm the influence of Gd ions in Au–polymer nanoparticles. As described previously,23 the presence of Gd ions enhances the Raman signal of biomolecules (protein, natural polymer) capped onto gold nanoparticles (AuNPs).…”
Section: Resultsmentioning
confidence: 87%
“…The interaction energies were calculated using the ab initio plane-wave pseudopotential approach as implemented in the VASP code 22. The Perdew–Burke–Ernzerhof (PBE) functional23 was chosen to perform the periodic DFT calculations, with accuracy on the overall convergence tested elsewhere 24. The valence electrons were treated explicitly and their interactions with the ionic cores are described by the Projector Augmented-Wave method (PAW),28,37,38 which allows the use of a low-energy cutoff equal to 400 eV for the plane-wave basis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lopez-Neira et al [271] observed that the SERS effect in L-tyrosine coated gold nanoparticles can be further enhanced by the coordination of Gd 3+ ions, after aggregation. The ~5 times enhancement promoted by the Gd 3+ ions was ascribed to the increase of the local electric field at the hot spot configuration.…”
Section: Ancillary Complexing Agentsmentioning
confidence: 99%
“…In SERS, a considerable enhancement of certain Raman bands is observed when the scattering molecules are adsorbed on rough metallic surfaces of nanoparticles of noble metals, e.g., Ag, Au and Cu. [1][2][3][4][5][6][7] The SERS effect is based mainly on two mechanisms: (1) a long-range electromagnetic (EM) effect and (2) a shortrange chemical (CHEM) effect/charge-transfer (CT) effect. The total enhancement is the result of both mechanisms (EM and CT).…”
Section: Introductionmentioning
confidence: 99%